Sinonasal Burkitt´s lymphoma – Case report - Barbosa, Marco Ribeiro (2011)
Non Hodgkin Lymphomas represent the second most frequent type of tumors in HIV (Human Immunodeficiency Vírus) positive patients, following Kaposi´s Sarcoma. Burkitt´s Lymphoma represents 30-40% of those cases. They preferencially affect the gastrointestinal tract and other extranodal sites. Some sinonasal cases have been described.Because of its highly aggressive behaviour, early diagnosis and treatment are crucial. We report the case of a 32 year old patient who presented with an apparent acute rhinosinusitis associated with unilateral periorbital cellulitis. Clinical and radiological evaluation revealed the cause of these features, actually, a mass, submitted to biopsy and involving both nasal cavities and nearby paranasal sinuses. He was then diagnosed sinonasal Burkitt´s lymphoma as inaugural manifestation of AIDS (Acquired ImmunoDeficiency Syndrome).He started treatment with antiretroviral drugs and chemoterapy, but died 7 days after, because of an acute myocardial infarction complicated by acute renal failure.